Studies on a Robotised Process for Forging Steel Synchronizer Rings in the Context of Forging Tool Life - Meller, Artur; Suszynski, Marcin; Legutko, Stanislaw; Traczynski, Marek; Cernohlavek, Vit (Manufacturing Technology Journal, 2023)
This paper proposes a solution not previously used in the forging industry, which aims to reduce the proportion of arduous human labour. The concept of a prototype robotic station for hot forging includes a system that allows the selection of batch material with its heating, the execution of the process of lu-brication of forging tools and the forging itself, synchronised with the feeding and removal of material using full automation, in accordance with the idea of Industry 4.0. At the same time, by increasing the repeatability of the entire forging process and changing some of its key parameters, it will be possible to influence the durability of the tools used during its implementation. In order to verify the impact of such a modified technological process on forging tool life, computer simulations of forging were performed, where the currently applied technology using hand forging was compared with a conceptual automated process.
Keywords: Die Forging; Automation; Forging Simulation; Tool Durability; Industry 4.0